Analisis Kebutuhan Pengembangan Media Pembelajaran Sex Education untuk Siswa Sekolah Dasar - Ilham (Journal of International Multidisciplinary Research, 2024)
The aim of this research is to analyze the need for developing sex education learning media for elementary school children. This research uses a qualitative descriptive research method. The data collection technique uses a questionnaire. Meanwhile, the data analysis uses qualitative data analysis. The results of the research show that (1) Currently there are not many sex education learning media that suit the characteristics of elementary school children, (2) it is very important to develop sex education learning media for elementary school children, (3) In general, sex education is still It is considered difficult to convey and teach to children. The causal factors include: First, parents' lack of understanding regarding sex education and how to provide information about Sex Education. Second, parents still feel embarrassed and uncomfortable conveying sexual matters to their children. Third, parents have not found the right tools that can be used to help and make it easier for them to introduce this matter.